Systems engineering and program management : trends and costs for aircraft and guided weapons programs - Stem, David E.; Boito, Michael; Younossi, Obaid; Project Air Force (U.S.). Resource Management Program; Rand Corporation; United States. Air Force (Santa Monica, CA : RAND, 2006)
Systems engineering and program management (SE/PM) constitute a large portion of the acquisition cost of military aircraft and guided weapons systems. The goal of this study was the development of a set of cost-estimating relationships that can be used to estimate the SE/PM cost element for development and production of aircraft and weapons programs. The authors canvassed government and industry personnel to learn about current techniques for estimating SE/PM costs, and they collected historical data from several aircraft and weapons programs to investigate trends in SE/PM costs over time and to generate methods that cost analysts can use early in the life cycle of a program when little cost information is available. The authors also investigated the effects on SE/PM costs from acquisition reform, including the reduction in the number of military specifications and standards, the use of integrated product and process teams, and the trend toward evolutionary acquisition."
"RAND Project Air Force."
Includes bibliographical references (p. 161-165).
Also available on the internet via WWW in PDF format.
Keywords: United States. -- Air Force -- Procurement -- Costs; Airplanes, Military -- United States -- Costs; Guided missiles -- United States -- Costs